2007
DOI: 10.1097/bot.0b013e31802cbc43
|View full text |Cite
|
Sign up to set email alerts
|

Complex Limb Salvage or Early Amputation for Severe Lower-Limb Injury: A Meta-Analysis of Observational Studies

Abstract: Functional outcome among patients who present with leg-threatening injuries are not significantly different, at least up to 7 years, whether they are managed with limb salvage or primary amputation. Research to optimize triage decisions to avoid failed limb salvage as well as on interventions targeting important psychosocial prognostic variables should be considered a priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
108
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 195 publications
(115 citation statements)
references
References 19 publications
3
108
1
3
Order By: Relevance
“…Akula, et al, performed a meta-analysis investigating amputation versus limb salvage from the patient's perspective, and noted that reconstruction is psychologically more acceptable [1]. Similar to Busse, et al, they reported there, were no significant between group differences for functional outcomes [1,7].…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Akula, et al, performed a meta-analysis investigating amputation versus limb salvage from the patient's perspective, and noted that reconstruction is psychologically more acceptable [1]. Similar to Busse, et al, they reported there, were no significant between group differences for functional outcomes [1,7].…”
Section: Discussionmentioning
confidence: 95%
“…More recently Doukas, et al (the METALS study) suggested that patients undergoing amputation had better functional outcomes than those undergoing limb salvage [11]. These findings are in contrast to Busse, et al, who performed a meta-analysis of observational studies comparing complex limb-salvage versus early amputation [7]. There was no difference between the two groups for functional outcomes at seven years, but the limb salvage group had a significantly longer rehabilitation time, more surgical procedures, and a higher rate of complications.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations